2009
DOI: 10.1111/j.1365-2567.2008.02898.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of N‐glycosylation in the kidney in a mouse model of systemic lupus erythematosus: relative quantification of N‐glycans using an isotope‐tagging method

Abstract: Summary Changes in the glycan structures of some glycoproteins have been observed in autoimmune diseases such as systemic lupus erythematosus (SLE) and rheumatoid arthritis. A deficiency of α‐mannosidase II, which is associated with branching in N‐glycans, has been found to induce SLE‐like glomerular nephritis in a mouse model. These findings suggest that the alteration of the glycosylation has some link with the development of SLE. An analysis of glycan alteration in the disordered tissues in SLE may lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Our glycoproteomics data indicate that sputum glycoproteins localizing to the specific and gelatinase granules and secretory vesicles in human neutrophils carried preferentially complex and high mannose N-glycans, suggesting a compartment-specific production and storage of paucimannosidic proteins in azurophilic granules. Highly similar N-glycosylation profiles of pathogeninfected sputum and neutrophil proteins, including the paucimannosidic profiles, further supported the neutrophilic origin of paucimannosylation and are congruent with studies indicating mammalian paucimannosylation in cancer and systemic lupus erythematosus (5,7,8,12), which are neutrophil-rich pathologies. The neutrophil N-glycosylation profile in our study resembles a previously reported human neutrophil N-glycan profile (48) in which the low mass paucimannosidic structures however were not reported.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our glycoproteomics data indicate that sputum glycoproteins localizing to the specific and gelatinase granules and secretory vesicles in human neutrophils carried preferentially complex and high mannose N-glycans, suggesting a compartment-specific production and storage of paucimannosidic proteins in azurophilic granules. Highly similar N-glycosylation profiles of pathogeninfected sputum and neutrophil proteins, including the paucimannosidic profiles, further supported the neutrophilic origin of paucimannosylation and are congruent with studies indicating mammalian paucimannosylation in cancer and systemic lupus erythematosus (5,7,8,12), which are neutrophil-rich pathologies. The neutrophil N-glycosylation profile in our study resembles a previously reported human neutrophil N-glycan profile (48) in which the low mass paucimannosidic structures however were not reported.…”
Section: Discussionsupporting
confidence: 64%
“…These structures do not correspond to the defined N-glycan types nor can their synthesis be described by established mammalian biosynthetic pathways. To date, mammalian protein paucimannosylation has been suggested to be present in (i) human buccal epithelial cells (4), (ii) human colorectal cancer epithelial cells and tissue (5-7), (iii) kidney tissue from mice suffering from systemic lupus erythematosus (8), (iv) mouse embryonic neural stem cells (9), and (v) rat brain (10). In addition, we recently indicated the presence of paucimannosylation in pathogen-infected sputum derived from individuals with cystic fibrosis (CF) 2 and upper respiratory tract infection (URTI) (11).…”
mentioning
confidence: 99%
“…The absorbance would thus underestimate the concentration of BAFF, because the capture Ab may mainly recognizes glycosylated BAFF. Previous studies have suggested that changes in N-glycan synthesis cause aberrant glycosylation in SLE-prone mice (37 ). High proportions of heterotrimers of BAFF and APRIL in SLE patients may also cause underestimation of BAFF (20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the degree of glycosylation and the content of mannose-binding lectin may be associated with the development of SLEassociated diseases in this murine model (56)(57)(58). By using the isotope-tagging method, we compared glycosylation of proteins in the disordered kidneys of the MRL-lpr mice with those in the normal kidneys of control mice (59).…”
Section: E Application To Glycomicsmentioning
confidence: 99%